Modeling subjective metrics for mobile evaluation - Hussain, Azham; Kutar, Maria; Abdul Mutalib, Ariffin; Mohmad Kamal, Fazillah (Information Service Systems Innovation (ISSI) research group, 2012)
There are several methods to evaluate mobile applications. The aim is to ensure that the applications are usable and satisfying users. Among the methods include lab test and field test.However, not many have focused on the quality characteristics should be used during the test.This study aims to develop subjective metrics for evaluation of mobile application using Goal Question Metric (GQM).To ensure the metrics we develop are reliable and useful, we conduct usability study that used the metrics we developed using GQM approach.The result indicates that the metrics can be used to evaluate mobile application in term of user satisfaction.Four test cases with different platforms employed in this study shows that the metrics are reliable to be used in mobile evaluation.